PENGARUH KOMUNIKASI INTERPERSONAL GURU TERHADAP MINAT BELAJAR SISWA KELAS XI SMA NEGERI 11 PEKANBARU - Fanny Alfrida Oktaviana Hutagaol; Hambali; Indra Primahardani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of teacher interpersonal communication on the learning interest of class XI students of SMAN 11 Pekanbaru. Interpersonal communication is one of the important things that teachers have in increasing student learning interest during the teaching and learning process. The existence of teacher communication with students will make the learning activities run better and have an impact on student learning interest. In the world of education, interpersonal communication is not only communication but must be interpreted by communicating the knowledge that exists in the teacher so that students can feel close to the teacher because of the openness between the teacher and the students. This study uses a quantitative descriptive method. The population in this study were 375 class XI students of SMAN 11 Pekanbaru. The sampling technique used simple random sampling with a sample size of 79 students. Data collection techniques used questionnaires and documentation. The data analysis technique used was simple linear regression. The results showed that teacher interpersonal communication had a significant effect on the learning interest of class XI students of SMAN 11 Pekanbaru. This is supported by a significance value of 0.000 <0.05 and an Fcount value of 33.319 ≥ Ftable 3.97. The coefficient of determination (R2) value is 0.302 or in percentage terms 30.2% while 69.8% is influenced by other variables not examined in this study.